Development of Android Based Halal Tourism Application For Travelers Using Scrum Method - A.M., Mursyidhan Ariefbillah; Afwani, Royana; Dwiyansaputra, Ramaditia; Saufi, Akhmad (Journal of Information System Research (JOSH), 2024)
Various strategies have been employed to rejuvenate the tourism industry, including enhancing halal tourism services. The halal tourism market segment is highly significant in terms of visitor number and expenditure during travel. This research addresses the technological challenges faced by halal tourism by developing an integrated Android application designed to facilitate hotel reservations, tourist transportation, tour packages, and access to halal-related information. Academics from several fields of University of Mataram play a crucial role in this project, serving as both Product Owners and Scrum Masters, guiding the development team, facilitating discussions, and ensuring the alignment of the application with halal tourism regulations. The application aims to enhance convenience and efficiency for Muslim Travelers by providing easy access to services and information, thus promoting more accessible and effective travel planning. This initiative supports the specific needs of Muslim Travelers and contributes to the economic growth and sustainability of halal tourism in the region. The User Interface (UI) and User Experience (UX) testing using the System Usability Scale (SUS) yielded a score of 82.5 with a grade "A". From the test results, it was concluded that the application, through the exploration of academic insights, is capable of producing an effective solution and meeting the needs of users, thereby improving the quality of services for tourists.